Analisis Strategi Marketing PT Bank Perkreditan Rakyat (BPR) Swadaya Anak Nagari untuk Menarik Minat Menabung Masyarakat : (Studi Kasus: Bandarejo Dusun 1) - Silva Nabila Putri; Novi Susanti; Yossi Eriawati (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to analyze the marketing strategy of PT Bank Perkreditan Rakyat (BPR) Swadaya Anak Nagari in attracting people's interest in saving money in Bandarejo Hamlet 1, West Pasaman Regency. A qualitative approach was used through field method with interviews, observation, and documentation. Research results showed that PT BPR Swadaya Anak Nagari implements four main marketing strategies: product strategy, price, and documentation. four main marketing strategies: product, price, promotion, and location strategies. Featured products such as KMB Savings (Kacio Mingguan Bajapuik) offers a savings collection service from the customer's home, making it easier for customers to save. service from the customer's home, providing convenience for people who find it difficult to reach bank locations. reach the bank's location. Direct promotion strategy through personal communication is the main key to success, building a close relationship between customers and the bank. bank. The strategic location of the bank office also contributes to the ease of access services. However, interest in saving, especially among teenagers and young adults, still low due to limited facilities such as ATM cards and mobile banking services. banking services. This finding highlights the need for the development of digital innovations to increase product appeal and expand market share. Research concluded that promotional strategies dominate in increasing the number of customers, while adapting to technology needs is a challenge to encourage wider to encourage wider interest in saving. This research provides important insights important insights for the management of marketing strategies in the local banking sector.